Arsenic biotransformation by Streptomyces sp. isolated from rice rhizosphere. (18th August 2014) - Kuramata, Masato; Sakakibara, Futa; Kataoka, Ryota; Abe, Tadashi; Asano, Maki; Baba, Koji; Takagi, Kazuhiro; Ishikawa, Satoru
Summary Isolation and functional analysis of microbes mediating the methylation of arsenic (As) in paddy soils is important for understanding the origin of dimethylarsinic acid (DMA) in rice grains. Here, we isolated from the rice rhizosphere a unique bacterium responsible for As methylation. Strain GSRB54, which was isolated from the roots of rice plants grown in As‐contaminated paddy soil under anaerobic conditions, was classified into the genus Streptomyces by 16S ribosomal RNA sequencing. Sequence analysis of the arsenite S‐adenosylmethionine methyltransferase (arsM) gene revealed that GSRB54 arsM was phylogenetically different from known arsM genes in other bacteria. This strain produced DMA and monomethylarsonic acid when cultured in liquid medium containing arsenite [As(III)]. Heterologous expression of GSRB54 arsM in Escherichia coli promoted methylation of As(III) by converting it into DMA and trimethylarsine oxide. These results demonstrate that strain GSRB54 has a strong ability to methylate As. In addition, DMA was detected in the shoots of rice grown in liquid medium inoculated with GSRB54 and containing As(III). Since Streptomyces are generally aerobic bacteria, we speculate that strain GSRB54 inhabits the oxidative zone around roots of paddy rice and is associated with DMA accumulation in rice grains through As methylation in the rice rhizosphere.